2021
DOI: 10.3389/fmicb.2021.725572
|View full text |Cite
|
Sign up to set email alerts
|

Nlrp3 Increases the Host’s Susceptibility to Tularemia

Abstract: Francisella tularensis (F. tularensis) is a Gram-negative, intracellular bacterium and the causative agent of a fatal human disease known as tularemia. The CDC has classified F. tularensis as a Tier 1 Category A select agent based on its ease of aerosolization, low infectious dose, past use as a bioweapon, and the potential to be used as a bioterror agent. Francisella has a unique replication cycle. Upon its uptake, Francisella remains in the phagosomes for a short period and then escapes into the cytosol, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…These findings established that Nlrp3 could be a prospective target for the development of effective therapeutics for tularemia (Suresh et al. 2021 ).…”
Section: Pathogenesismentioning
confidence: 78%
“…These findings established that Nlrp3 could be a prospective target for the development of effective therapeutics for tularemia (Suresh et al. 2021 ).…”
Section: Pathogenesismentioning
confidence: 78%
“…Hap-I and Hap-II TG adult and old mice were infected intranasally with 1 × (1 × 10 4 CFU) and 10× (1 × 10 5 CFU) lethal doses of F. tularensis LVS and were observed for morbidity and mortality for 15 days post-infection. The infection doses selected were based on our several previous studies ( Alqahtani et al, 2018 ; Ma et al, 2019 ; Marghani et al, 2021 ; Suresh et al, 2021 ). No differences between the survival proportions of Hap-II TG adult and old mice were observed, and 60 % of mice from both groups succumbed to infection with 1 × 10 4 CFUs of F. tularensis LVS with a median survival time (MST) of 12 days.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed global and tissue-specific transcriptomic alterations related to aging and infections ( Lee et al, 2002 ; Rodwell et al, 2004 ; Alfego et al, 2018 ; Suresh et al, 2021 ). However, these studies do not provide molecular insight into hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced activity of UCH-L5 might result in suppressing activation of NLRP3 inflammasome in the early phase of infection. In the later phases of infection, however, it was found that the NLRP3 reduces NF-kB and MAPK signaling, thereby promoting Francisella's replication inside infected macrophages (44). USP25, a ubiquitin-specific protease, plays a role, besides others, in bacterial infection (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%